Chucking in Evelyn Waugh. Issue 5 (28th May 2018) - Carver, Beci
ABSTRACT: For Tony Last in Waugh's Handful of Dust (1934), the world divides itself into 'chuckers' and 'non-chuckers'; he commiserates tipsily with a new friend: 'you feel low because your girl's chucked, and I feel low because mine won't chuck.' To 'chuck', in Waugh's writing and in early-to-mid twentieth-century slang more generally, was to abandon a commitment – whether a marriage, a party, or a choice of hat. One could chuck anything or anyone. And this article will venture that one of the ways in which Waugh's 'lost generation' performed their loss or lostness was often to chuck. Chucking was proactive, in a sense, while also predominantly last-minute and slapdash. It rarely asked to be taken seriously; indeed, its resistance to norms of responsible behaviour could be offensive. Waugh complains in 1960: 'People keep writing to say they are coming to stay with me and I get very excited & have my hair cut in Taunton and buy smoked salmon & and then they chuck.' However, ironically enough, the habit of chucking could be difficult to chuck. Chucking proved to be ineffectual when turned against itself.